The Psychological Experience and Intervention in Post-Acute COVID-19 Inpatients - Rossi Ferrario S (Dove Medical Press, 2021)
Silvia Rossi Ferrario,1,* Anna Panzeri,1,2,* Paola Cerutti,1 Daniela Sacco1 1Psychology and Neuropsychology Unit, Institute of Veruno, Istituti Clinici Scientifici Maugeri IRCCS, Veruno, Italy; 2Department of General Psychology, University of Padova, Padova, Italy*These authors contributed equally to this workCorrespondence: Anna PanzeriDepartment of General Psychology, University of Padova, Padova via Venezia 8, Padova, 35131, ItalyEmail anna.panzeri@phd.unipd.itPurpose: COVID-19 patients faced first-hand the life-threatening consequences of the disease, oftentimes involving prolonged hospitalization in isolation from family and friends. This study aimed at describing the psychological intervention to address the psychological difficulties and issues encountered by the hospitalized post-acute COVID-19 patients in a rehabilitation setting.Patients and Methods: Patients’ demographics, medical diagnosis, and neuro-psychological information were collected from March 2nd to May 12th, 2020. The main psychological issues and intervention strategies were collected.Results: A total of 181 patients were hospitalized during this period. Among them, the 47.5% underwent psychological assessment (N=86; age: 74.58± 13.39; 54.7% females). The most common psychological issues were acute stress disorders (18.6%), anxious and demoralization symptoms (26.7%), depression (10.5%%), and troublesome grief (8.1%). Once recovered from COVID-19, many patients were discharged home (38.4%), some received further rehabilitation in non-COVID-19 wards (41.9%), mostly due to pre-existent diseases (72.2%) rather than to COVID-19 complications (27.8%).Conclusion: A great number of the hospitalized post-acute COVID-19 patients showed psychological issues requiring psychological intervention, the most common were anxiety, demoralization, acute stress, depression, and grief. The proposed psychological treatment for hospitalized COVID-19 patients was conducted in a Cognitive Behavioral framework. In particular, during the COVID-19 pandemic, psychological intervention is an important part of rehabilitation in the post-acute phase of the illness to reduce distress symptoms and improve psychological health.Keywords: psychological intervention, COVID-19 patients, clinical psychology, health psychology, rehabilitation